Laser 3D Printing with Sub‐Microscale Resolution of Porous Elastomeric Scaffolds for Supporting Human Bone Stem Cells. Issue 5 (17th December 2014) - Petrochenko, Peter E.; Torgersen, Jan; Gruber, Peter; Hicks, Lucas A.; Zheng, Jiwen; Kumar, Girish; Narayan, Roger J.; Goering, Peter L.; Liska, Robert; Stampfl, Jürgen; Ovsianikov, Aleksandr
<x xml:space="preserve">Abstract</x> A reproducible method is needed to fabricate 3D scaffold constructs that results in periodic and uniform structures with precise control at sub‐micrometer and micrometer length scales. In this study, fabrication of scaffolds by two‐photon polymerization (2PP) of a biodegradable urethane and acrylate‐based photoelastomer is demonstrated. This material supports 2PP processing with sub‐micrometer spatial resolution. The high photoreactivity of the biophotoelastomer permits 2PP processing at a scanning speed of 1000 mm s−1, facilitating rapid fabrication of relatively large structures (>5 mm3). These structures are custom printed for in vitro assay screening in 96‐well plates and are sufficiently flexible to enable facile handling and transplantation. These results indicate that stable scaffolds with porosities of greater than 60% can be produced using 2PP. Human bone marrow stromal cells grown on 3D scaffolds exhibit increased growth and proliferation compared to smooth 2D scaffold controls. 3D scaffolds adsorb larger amounts of protein than smooth 2D scaffolds due to their larger surface area; the scaffolds also allow cells to attach in multiple planes and to completely infiltrate the porous scaffolds. The flexible photoelastomer material is biocompatible in vitro and is associated with facile handling, making it a viable candidate for further study of complex 3D‐printed scaffolds.